The impact of inter-vehicle communication on vehicular traffic - Killat, Moritz (KIT Scientific Publishing, 2009)
The work addresses communication networks established over radio equipped vehicles in our everyday road traffic, so called Vehicular Ad Hoc Networks (VANETs), and discusses their impact on two major goals, namely traffic safety and traffic efficiency. For both objectives, the thesis proposes an appropriate modeling of the essential building blocks Traffic, Communication and Application and enables impact assessment studies by means of implemented simulation tools.